Prevalence and Factors of Burnout among Australian Orthopaedic Trainees: A Cross-Sectional Study. (December 2014) - Arora, Manit; Diwan, Ashish D; Harris, Ian A
Purpose: To assess the prevalence and factors of burnout among Australian orthopaedic trainees. Methods: 236 orthopaedic registrars of the Australian Orthopaedic Association were invited to participate in a 32-item survey by email. The questionnaire assessed potential factors associated with burnout, satisfaction with the choice of orthopaedics as a career and work-life balance, and subjective overall health, as well as 3 subscales of the Maslach Burnout Inventory – Human Services Survey for assessing burnout: emotional exhaustion, depersonalisation, and personal accomplishment. Participants with high levels of either emotional exhaustion or depersonalisation were defined as having burnout. Those with and without burnout were compared. Results: 51 (22%) of the 236 trainees completed the questionnaire. Of whom, 88% were satisfied with their choice of orthopaedics as a career, whereas 27% were satisfied with their work-life balance. 27 (53%) respondents were considered burned out. Compared with those who did not burn out, those who burned out were less satisfied with their careers (p=0.004) and work-life balance (p=0.021). Conclusion: 53% of Australian orthopaedic trainees were burned out. Burnout trainees were more likely to be dissatisfied with their career choice and work-life balance. Active interventions to combat burnout and improve work-life balance are needed.